6 - Excess Beyond Excellence: The University Beyond the Balance Sheet - Kistner, Ulrike (Journal of Higher Education in Africa, 2007)
This paper argues that there is an excess beyond the talk of excellence, that the University in its present drive for commodification and corporatisation cannot com- prehend. In outlining the conditions and effects of this excess, I will look at the non- symmetrical relation that plays itself out in teaching and learning as one of the sites of ethical practices. The notions adduced to analyse this core relation are those of charisma, transference and sublimation. I will outline the forms of exchange at work in the sites of this relation and analyse their differentiations and transformations. In as much as the teaching–learning relation encapsulates what is demanded psycho- logically and politically of a modern subject in a democratic order, jeopardising it in the name of efficiency, cost-cutting and an instrumentalised relationship to la- bour and commodity markets, means striking not only at the core of university education, but at the psychic and political foundations of a democratic order itself.